2002
DOI: 10.1046/j.1365-246x.2002.01696.x
|View full text |Cite
|
Sign up to set email alerts
|

Separation of intrinsic and scattering seismic attenuation in the Southern Apennine zone, Italy

Abstract: Summary Scattered waves observed at the seismographs of the National Italy's seismic network have been used to investigate the intrinsic dissipation and scattering properties of the lithosphere under the Southern Apennines, Italy. First, we investigate the coda‐Q properties, then we apply the MLTW analysis in the hypothesis of velocity and scattering coefficient constant with depth, and finally we interpret these results with the aid of numerical simulations in a medium with depth dependent velocity and scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
66
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 28 publications
9
66
1
Order By: Relevance
“…The quality factor Q based on the S-wave part of the recordings shows a pronounced frequency-dependence (close to linear), given by Q( f ) = 28.3 f 0.87 . This S-wave attenuation model differs from the results of other authors reported for neighboring regions (Rovelli et al, 1988;Malagnini et al, 2000;Bianco et al, 2002), and in particular shows a less severe frequency-dependence than the results derived by Castro et al (2004bCastro et al ( , 2008 for southern Italy. However, as stated above, it is important to keep in mind that the comparison of different models is complicated by the fact that the data used to estimate them sample different frequency bands and different crustal volumes.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The quality factor Q based on the S-wave part of the recordings shows a pronounced frequency-dependence (close to linear), given by Q( f ) = 28.3 f 0.87 . This S-wave attenuation model differs from the results of other authors reported for neighboring regions (Rovelli et al, 1988;Malagnini et al, 2000;Bianco et al, 2002), and in particular shows a less severe frequency-dependence than the results derived by Castro et al (2004bCastro et al ( , 2008 for southern Italy. However, as stated above, it is important to keep in mind that the comparison of different models is complicated by the fact that the data used to estimate them sample different frequency bands and different crustal volumes.…”
Section: Discussioncontrasting
confidence: 95%
“…The studies by Malagnini et al (2000) and Rovelli et al (1988) sample for 12 instance large regions such as the entire Apennines or the entirety of southern Italy. In contrast, our results are related to a small area limited by the extent of the ISNet network, and also Bianco et al (2002) analyzed data from a much larger area surrounding the ISNet network. This limitation of our study to the small region covered by the ISNet network can however also be seen as an advantage in the sense that with the derived attenuation functions, we provide a means for reliable and consistent attenuation correction for events occurring in close proximity or within the network, avoiding a bias in source parameter or site response estimation due to inappropriate attenuation correction.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…F 60 denotes the Fisher distribution function with a confidence level of 60%, which was also used by previous studies (Bianco et al, 2002(Bianco et al, , 2005Giampiccolo et al, 2006). The ratios M f ðZ s ; Z i Þ=M f ðẐ s ;Ẑ i Þ were depicted by the shading zones for the confidence areas ( Figure 5).…”
Section: Eventmentioning
confidence: 99%
“…Thirdly, we compare the integrated energy densities derived from observational data with that derived from theoretical formulation to obtain the best-fitting values of B 0 and L −1 e . The fitting errors are calculated by the following equation (Bianco et al, 2002):…”
Section: The Calculation Of Scattering Coefficientmentioning
confidence: 99%